(untitled) (Journal of Engineering, 2016)
This thesis aims to study the effect of addition polymer materials on mechanical properties of self-compacting concrete, and also to assess the influence of petroleum products (kerosene and gas oil) on mechanical properties of polymer modified self-compacting concrete (PMSCC) after different exposure periods of (30 ,60 ,90 ,and 180 days). Two type of curing are used; 28 days in water for SCC and 2 days in water followed 26 days in air for PMSCC. The test results show that the PMSCC (15% P/C ratio) which is exposed to oil products recorded a lower deterioration in compressive strength’s values than reference concrete. The percentages of reduction in compressive strength values of PMSCC (15% P/C ratio) was (6.03%) and (9.61%) up to 180 days of exposure to kerosene and gas oil respectively, relative to the same mix immersed in water, while the percentages of reduction in compressive strength values of SCC (reference concrete) was (21.18%) and (25.19%) up to 180 days of exposure to kerosene and gas oil respectively, relative to the same mix immersed in water. Flexural strength results present improvement for all ages and for all concrete mixes with all percentages of polymer content. The total water absorption values of PMSCC (15% P/C ratio) showed a better performance than reference concrete mix when exposed to oil products. It was (1.34, 2.21, 2.17) % up to 180 days with samples immersed in water, kerosene, and gas oil respectively, with percentages of reduction of (23.86%), (33.83%), and (31.33%) relative to the SCC (reference concrete).